Pengaruh Perencanaan Pajak, Aset Pajak Tangguhan, Dan Profitabilitas Terhadap Manajemen Laba - Noorjannah Vira Astuti; Rachmawati Meita Oktaviani (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
This study aims to measure the effect of tax planning, deferred tax assets and profitability on earnings management in manufacturing companies. This research is a quantitative research. The data used in this study are secondary data obtained from annual financial reports. The population used is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2017 - 2019. The sample in this study was selected using purposive sampling technique, namely samples selected based on certain criteria. The sample used in the study was 50 companies in the manufacturing sector. The data analysis technique used in this study used multiple linear regression analysis with the help of the IBM SPSS 25.0 program. The results show that tax planning has a negative and insignificant effect on earnings management, deferred tax assets have a negative and insignificant effect on earnings management, and profitability has a positive and significant effect on earnings management. Keywords: Profit Management, Tax Planning, Deferred Tax Assets, Profitability